Attaching DNA to Gold Nanoparticles With a Protein Corona - Wu, Rong; Peng, Huaping; Zhu, Jun-Jie; Jiang, Li-Ping; Liu, Juewen (Frontiers in Chemistry, 2020)
DNA-functionalized gold nanoparticles (AuNPs) have been widely used in directed assembly of materials, biosensors, and drug delivery. This conjugate may encounter proteins in these applications and proteins may affect not only DNA adsorption but also the function of the attached DNA. Bovine serum albumin (BSA) with many cysteine residues can strongly adsorb on AuNPs and this conjugate showed high colloidal stability against salt, acid and base. Similar protection effects were also observed with a few other common proteins including catalase, hemoglobin, glucose oxidase, and horseradish peroxidase. DNA oligonucleotides without a thiol label can hardly displace adsorbed BSA, and BSA cannot displace pre-adsorbed DNA either, indicating a strongly kinetically controlled system. Thiolated DNA can be attached at a low density on the AuNPs with a BSA corona. The BSA corona did not facilitate the hybridization of the conjugated DNA, while a smaller peptide, glutathione allowed faster hybridization. Overall, proteins increase the colloidal stability of AuNPs, and they do not perturb the gold-thiol bond in the DNA conjugate, although a large protein corona may inhibit the hybridization function of DNA.